Odyssey to the Model Norwegian State: De/Constructing Migration Journeys Step-by-Step from Students’ Digital Stories - Kristine Øygardslia; Priscilla Ringrose (Nordic Journal of Migration Research, 2023)
This article examines digital stories about migration journeys produced by students in a mainstream upper secondary class in Norway. The digital stories were introduced as part of a social studies module designed to foster critical thinking around migration. The class was made up of ethnic Norwegian students, students with a family migration background, and recently arrived migrant students. Using multimodal analysis, we examined the storylines in the students’ digital stories, focusing on the understandings of migration and nation produced. Inspired by Bamberg’s (2004) conceptualisation of dominant and counter narratives, we explored the extent to which these understandings interpellated/resisted dominant narratives of migration and nation. We asked: What understandings of the migrant and of Norway do the storylines re/produce? To what extent do these understandings draw on dominant Norwegian narratives of migration? Our findings suggest that most of the digital stories draw on dominant narratives, especially that of Norway as an idealised model state. In conclusion, we discuss possible reasons for the narrative standardisation and suggest potential ways of opening up educational spaces for more counter narratives.